Seroprevalence of Helicobacter pylori infection among children and their parents in eastern Turkey - Yilmaz, E; Dogan, Y; Gürgöze, MK; Ünal, S (Wiley, 2002)
Objectives : To determine the seroprevalence of Helicobacter pylori infection among healthy children in eastern Turkey, to assess risk factors for seroconversion, and to assess the role of parental infection status in the transmission of H. pylori . Methods : A commercial enzyme immunoassay test for IgG to H. pylori was used. Demographic information obtained included age, gender, socio-economic status and living conditions. Results : One hundred and fifty-two (43.9%) of 346 children were seropositive. There was no significant difference in rates of seroprevalence between boys and girls (P > 0.05), but a significant rise was noted with increasing age (P < 0.001). We found a strong inverse correlation between family income and seropositivity (P < 0.001). Seroprevalence also varied significantly with the educational level of the mother (P < 0.001). There were no significant differences in seroprevalence associated with place of residence, water supply and the number of persons per room (P > 0.05). The prevalence of infection in the corresponding parents was 85.4% for mothers and 76.3% for fathers. Seroprevalence was higher in children whose mother was infected (P < 0.001). Conclusions : In eastern Turkey, as in other developing countries, H. pylori infection occurs early and increases with age. Infected parents, especially infected mothers, may have a important role in the transmission of H. pylori within families.
Keywords: Helicobacter pylori; seroprevalence